Interrater Reliability and Concurrent Validity of the Risk for Sexual Violence Protocol for Korean Sexual Offenders: A Field Study. (October 2021) - Sea, Jonghan; Hart, Stephen D.
The Risk for Sexual Violence Protocol (RSVP) is a set of structured professional judgment guidelines for conducting management-oriented sexual violence risk assessments. We investigated the interrater reliability (IRR) and the concurrent validity of the RSVP in the Republic of Korea. A total of 32 experienced and specially trained correctional psychologists in teams of four used an authorized translation of the RSVP to independently assess 47 adult male sexual offenders through a case history review and interviews. IRR, as indexed using intraclass correlations coefficients, was typically good to excellent for rating the presence and relevance of risk factors. Concurrent validity was also good, as indexed by correlations between RSVP ratings and total scores on two instruments for assessing risk for sexual violence: the Hallym Assessment Guide for Sex Offender Risk and Static-99R. Implications for the use of the RSVP by professionals and agencies, both within and outside Korea, are discussed.